Syntax and Semantics of Korean Null Subjects and Null Objects - Kang, Namkil; Kim, Dae Hwan (Forum for Linguistic Studies, 2025)
This article argues that Korean null subjects and objects should not be treated as instances of pro. Instead, we propose that these elements are distinct null arguments, with their reference determined pragmatically rather than syntactically. To support this claim, we analyze the behavior of null subjects in embedded clauses. We suggest that these null subjects function as free variables, with their referents being chosen based on the speaker’s intention and the broader pragmatic context, rather than through syntactic binding or fixed discourse anaphora. We also highlight important semantic differences. Null subjects tend to favor de se readings (where the referent is self-aware), while overt pronouns lean toward de re readings (where the referent is interpreted as an external entity). Furthermore, null subjects can be interpreted as bound variables under quantification, while overt pronouns generally resist such interpretations, reinforcing the syntactic distinction between the two. Additional evidence comes from maximality effects and dual readings. Overt pronouns usually exhibit stronger maximality effects and allow for dual readings when the plural suffix -tul is added, while null subjects do not show the same interpretive flexibility. These differences demonstrate that null and overt pronouns operate according to distinct interpretive mechanisms. Taken together, these findings challenge pro-based analyses and support the idea that Koreannull arguments represent a unique syntactic and semantic category. We advocate for a null argument hypothesis in Korean grammar that captures these distinctions and deepens our understanding of null argument phenomena across languages.